LARVAL DEVELOPMENT OF THE INDONESIAN BLUE SWIMMING CRAB, PORTUNUS PELAGICUS (L) (CRUSTACEA : DECAPODA : PORTUNIDAE) REARED IN THE LABORATORY - Juwana, Sri; Aswandy, Indra; Pangabean, M.G. Lily (Marine Research in Indonesia, 1987)
A number of 137,870 freshly hatched larvae of Portunus pelagicus (L) were reared in one thousand litre container. The combination of Brachionus plicatilis and newly hatched nauplii of Artemia salina were fed to the larvae. The number of megalopa obtained was only 277. Ecological factor such as temperature, salinity, pH and dissolved oxygen were recorded. The effect of different food sources of the previous authors are compared. The detail description of the four zoeal stages and one megalopal stage are made and figured with emphasis on the number and type of setae on each appendages. A pattern of zoeal chromatophores is also sketched and described.